A Cross-Sectional Analysis of Students’ Intuitions When Interpreting CIs - Kalinowski, Pav; Lai, Jerry; Cumming, Geoff (Frontiers in Psychology, 2018)
We explored how students interpret the relative likelihood of capturing a population parameter at various points of a CI in two studies. First, an online survey of 101 students found that students’ beliefs about the probability curve within a CI take a variety of shapes, and that in fixed choice tasks, 39% CI [30, 48] of students’ responses deviated from true distributions. For open ended tasks, this proportion rose to 85%, 95% CI [76, 90]. We interpret this as evidence that, for many students, intuitions about CIs distributions are ill-formed, and their responses are highly susceptible to question format. Many students also falsely believed that there is substantial change in likelihood at the upper and lower limits of the CI, resembling a cliff effect (Rosenthal & Gaito 1963). In a follow-up study, a subset of 24 post-graduate students participated in a 45 minute semi-structured interview discussing the students’ responses to the survey. Analysis of interview transcripts identified several competing intuitions about CIs, and several new CI misconceptions. During the interview, we also introduced an interactive teaching program displaying a cat’s eye CI, that is, a CI that uses normal distributions to depict the correct likelihood distribution. Cat’s eye CIs were designed to help students understand likelihood distributions and the relationship between interval length, C% level and sample size. Observed changes in students’ intuitions following this teaching program suggest that a brief intervention using cat’s eyes can reduce CI misconceptions and increase accurate CI intuitions.